(3GdNQGLs - (3bOGeI Hf LYaQ Hf bOGeI Hf RjGO GdHZOGOj, CHh GdaQL,J (B337 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd ai OjhGf GdLjT s
(3BNQgG (B:s
(3GdHGH GdMGOi YTQ ai OjhGf GdHQjI hGdScI hGdWQb Edi fhGMi GdeTQb hGdeZQH s
(3GdehLhOI bWYI efgs
(3JcQQJ CjVkG JMJ Qbe (B646 (3JGQjNs
(3fSNI ahJhZQGajI eUhQI Yf fSNI HGQjSs
(3hgh eQJH Ydi KeGfi efGRd cd efRdI JTJed Ydi CHhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B128s
Keywords: (3GdJGQjNs